Reducing Health Disparities: What Is Being Done, What Works - William Baldyga, DrPH, MA; Karen Petersmarck, PhD, MPH (Centers for Disease Control and Prevention, 2005)
If necessity is the mother of invention, creativity in public health has never been more important. Fortunately, the ability of the public health thinkforce (as compared to workforce) to respond to the challenges inherent in assuring the publics health is remarkable. The willingness of the thinkers to share information has always been a strength of the field, and now new technologies have enhanced our abilities to communicate what works, for whom, and under what conditions. Challenges to population health continue to mount. Risk factor increases (e.g., obesity) and poorer access to services (e.g., percentage of population without insurance) conspire with multiple other health determinants to create monumental challenges for public health, particularly in the area of health disparities. Understanding disparities their roots and their implications is a difficult challenge; our future success will be largely determined by our response to this challenge. Correcting disparities will require, in part, the best application of chronic disease program knowledge to the populations at greatest risk.